ANALYZING BIOPSYCHOSOCIAL FACTORS INFLUENCING SELF-MANAGEMENTBEHAVIORS OF PATIENTS UNDERGOING HEMODIALYSIS - Merry Tiyas Anggraini; Aisyah Lahdji (Program Studi Ilmu Keperawatan Universitas Jember, 2025)
Background:Continuous hemodialysis is a lifelong treatment, causing medical, psychological, social, and economic consequences for patient. Effective self-management is a critical strategy to improve patient outcomes, as it empowers individuals to actively participate in their care. Strong selfmanagement is directly linked to better adherence, fewer treatment-related complications, an enhanced quality of life by giving patients greater control over their condition. Objective: Aimed to investigate biopsychosocial factors that influence hemodialysis patients' self-management practices. Methods: This study utilized a cross-sectional, observational analytical design. Psychological factors were self-efficacy, depression, social factors were family support. Data were collected using a questionnaire and analyzed to find associations with self-management behavior. Chi-square test was used for categorical biological factors, while the Spearman's rank test was used to analyze relationship with ordinal variables of family support, self-efficacy, depression. Results: There is a correlation between self-management behavior with education level (p=0.035), occupation (p=0.031), marital status (p=0.048), family support (p=0.039), depression (p=0.001), and self-efficacy (p=0.001). Self-management behavior is unrelated to age (p=0.538), gender (p=0.273), length of illness (p=0.529), length of hemodialysis (p=0.529), complications (p=0.675), and comorbidities (p=0.694). Conclusion: There is a relationship betweeneducation level, occupation, marital status, family support, depression, selfefficacy with self-management behavior in CKD patients undergoing hemodialysis at KRMT Wongsonegoro Hospital, Semarang.